REPRESENTATION OF ONLINE LEARNING IN COMIC STRIP CHITATO MAXX BY TAHILALATS - Hiu, Elisiah Marsanda; Dessen, Denia (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2022)
The emergence of many new innovations in the manufacture of products and services creates competition in forming attractive advertisements so that the target market is achieved. The development of social media has become a platform for the emergence of content creators who have creative and entertaining ideas, one of which is the creator of digital comic strips. This opens up opportunities for entrepreneurs to use comic strips as a medium for promoting their products. An example is the Chitato Maxx comic strip commercial. A comic strip in its concept can contain about social problems, but with a humorous nature. This happened in the Chitato Maxx comic strip advertisement with the concept of online learning. This study analyzes the meaning of denotation, connotation, and myth in Roland Barthes' semiotics in Chitato Maxx advertisements to find out the representation of online learning presented in the advertisements. In the results of the study, the comic strip advertisement represents online learning by displaying the behavior of students and teachers when conducting online meetings. The advantages of Chitato products are also present even though the advertising concept contains social issues